Epigenetic Modifications in Essential Hypertension - Wise, Ingrid A. (Int J Mol Sci, 2016)
Essential hypertension (EH) is a complex, polygenic condition with no single causative agent. Despite advances in our understanding of the pathophysiology of EH, hypertension remains one of the world’s leading public health problems. Furthermore, there is increasing evidence that epigenetic modifications are as important as genetic predisposition in the development of EH. Indeed, a complex and interactive genetic and environmental system exists to determine an individual’s risk of EH. Epigenetics refers to all heritable changes to the regulation of gene expression as well as chromatin remodelling, without involvement of nucleotide sequence changes. Epigenetic modification is recognized as an essential process in biology, but is now being investigated for its role in the development of specific pathologic conditions, including EH. Epigenetic research will provide insights into the pathogenesis of blood pressure regulation that cannot be explained by classic Mendelian inheritance. This review concentrates on epigenetic modifications to DNA structure, including the influence of non-coding RNAs on hypertension development.